Development of a measurement metric for manufacturing process robustness. (4th August 2010) - Mondal, S.C.; Maiti, J.; Ray, P.K.
Literature on the study on manufacturing process robustness is limited. Very often, process robustness is dealt with single-stage process and considers a single response variable. Moreover, the effect of operators and equipment on the overall process robustness is seldom studied. These shortcomings have led to the development of a new measurement metric for evaluating manufacturing process robustness which is presented in this study. The proposed metric considers the effects of input raw material, process operating conditions and equipment and operator performances in its development. The metric can be used for analysing both univariate and multivariate data. Partial contribution indices and multivariate S/N ratio are also developed. Three case studies were conducted in centrifugal casting, heat treatment and forging shops. From the results, it is also clear that when the robustness of a process increases, the multivariate S/N ratio increases and the transmitted variation reduces.